Going first class? : new approaches to privileged travel and movement - Amit, Vered (EASA series, 2011)
People travel as never before. However, anthropological research has tended to focus primarily on either labor migration or on tourism. In contrast, this collection of essays explores a diversity of circumstances and impetuses towards contemporary mobility. It ranges from expatriates to peripatetic professionals to middle class migrants in search of extended educational and career opportunities to people seeking self development through travel, either by moving after retirement or visiting educational retreats. These situations, however, converge in the significant resources, variously of f.